Characterizing Effects of Ingredients Differing in Ruminally Degradable Protein and Fiber Supplies on the Ovine Rumen Microbiome Using Next-Generation Sequencing - Gleason, Claire B.; Settlage, Robert E.; Beckett, Linda M.; White, Robin R. (Frontiers in Animal Science, 2021)
The ratio of concentrate to forage within diets is known to alter rumen microbial profiles, but comparatively less information is available on the effect of differing sources of individual nutrients on the microbiome. The objective of this study was to investigate rumen microbial responses to diets composed of protein and fiber sources expected to vary in nutrient degradability. The responses of interest included relative abundances of bacterial taxa as well as estimations of community richness and diversity. Ten ruminally cannulated wethers (Suffolk, Dorset, or Suffolk × Dorset) received four diet treatments consisting of either beet pulp or timothy hay and soybean meal (SBM) or heat-treated soybean meal (HSBM) in a partially replicated 4 × 4 Latin square experiment for 21 days. Timothy hay and beet pulp were expected to provide differing rumen degradabilities of neutral detergent fiber (NDF) while the soybean meals were expected to provide differing rumen degradabilities of crude protein (CP). Solid and liquid samples of rumen contents were collected for microbial DNA isolation and Next-Generation sequencing. Numerous rumen bacterial population shifts were observed due to change in fiber source, with increased abundances (P < 0.05) of fibrolytic populations associated with timothy hay diets compared with beet pulp diets. Conversely, populations of the pectin-degrading genera, Treponema and Lachnospira, increased on the beet pulp treatment (P = 0.015 and P = 0.0049, respectively). Limited impact on bacterial taxa was observed between diets differing in protein source. The Paraprevotellaceae genus YRC22 was observed to increase in abundance on HSBM diets (P = 0.023) and the phylum Spirochaetes tended to be more abundant on SBM than HSBM diets (P = 0.071). Beet pulp decreased rumen bacterial diversity (P = 0.0027) and tended to decrease bacterial species richness (P = 0.051) compared to timothy hay. Our results serve to further underscore the sensitivity of rumen microbes to changes in their preferred substrates, particularly of those associated with fiber degradation.